IMITATING MODELING OF REPRODUCTION AS A TOOL OF STATE SUPPORT OF AGRICULTURAL ENTERPRISES - Kostuchenko Tatyana Nikolaevna; Sidorova Darya Vladimirovna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2013)
It is now one of the main conditions to ensure food security in Russia is a stable development of the domestic production of high-quality agricultural products, which is the basis for the stability of the reproductive process in agriculture. The aim of the present work is to determine the parameters of rational reproduction through the use of simulation as well as the rationale for the most appropriate areas of state support for enterprises of the agrarian sector. The set of methodological and practical aspects of the process of reproduction in agriculture acts as a research subject. The object of the study are the large and medium-sized agricultural enterprises second natural-economic zone of the Stavropol Territory. The novelty of the work lies in the fact that the authors have developed a simulation model for predicting the process of reproduction, the use of which allows us to estimate the change of its parameters in the future, taking into account the impact of various economic factors. The study proposed differentiation of state support of agricultural producers, depending on the type of reproduction provided with them and with the requirements of the WTO.